Cognitive behavioral group therapy for social anxiety disorder: Effectiveness study at the Icelandic center for Treatment of Anxiety disorders for youths - Ásdís Magnea Egilsdóttir 1988- (2018)
Social anxiety disorder (SAD) is one the most common anxiety disorders in adolescence and can have inhibiting impact on individuals life. The purpose of this research study was to examine the effectiveness of cognitive behavioral group therapy (CBGT) for adolescents with SAD in Iceland. The participants consisted of 32 Icelandic adolescents with a mean age of 17 years (sd = 0.96), who completed four questionnaires assessing social- and general anxiety, and depression symptoms before treatment, after treatment, and at four-weeks follow-up. The participant’s scores were summarized and compared across time and effect sizes were calculated. Finally, it was examined whether the treatment leads up to clinically significant changes. The results revealed that the participant’s anxiety and depression symptoms decreased over time indicating that the group CBT was effective. These results support the hypothesis of the current study which was that participants would experience less social anxiety, general anxiety, and depression symptoms following the treatment. Effect sizes indicated a great treatment effect on SAD symptoms among the participants from pretest to posttest (d = 0.96, d = 1.15). Furthermore, the proportion of participants reporting clinical level of anxiety and depression decreased after the treatment. Keywords: Social anxiety, cognitive behavioral therapy, group therapy, adolescents, anxiety, impact assessment. Félagsfælni er ein algengasta kvíðaröskunin meðal unglinga og getur haft töluvert hamlandi áhrif á þann sem upplifir hana. Tilgangur rannsóknarinnar var að kanna áhrif hugrænnar atferlismeðferðar í hóp við félagsfælni meðal unglinga á Íslandi. Þátttakendur voru 32 unglingar að meðalaldri 17 ára (sf = 0.96). Borin voru saman skor þátttakenda við upphaf og lok meðferð og í 4 vikna eftirfylgd á spurningalistum sem meta félagsfælni (samskipta- og frammistöðukvíða), almennan kvíða og þunglyndi og áhrifastærðir (effect sizes) voru reiknaðar fyrir mun á meðalskorum þátttakenda. Að lokum var kannað hvort að ...